Microfluidic devices for gene preparation and detection - Xu, Guolin (2014)
Lab-on-a-chip systems can be used to conduct various biological and chemical processes for point-of-care diagnostics. The present thesis focuses on the development of methods and devices for automatic bio-sample preparation and detection with lab-on-a-chip systems. Firstly, a completely sealed cartridge, which contains all the reagents necessary for DNA/RNA sample preparation, has been developed. The entire sample preparation process can be completed automatically within 6 minutes on a desktop unit. Transferring of reagents between chambers is achieved using a combination of push and pull forces generated by compressed air and vacuum, respectively. The required pressure for transferring the sample preparation solutions is calculated and compared to experimental measurements. The on-cartridge DNA recovery efficiency is 54–63%, which is comparable to or even higher than the conventional manual approach using silica spin column. An all-in-one system has been developed for rapid influenza diagnosis by integrating the automatic sample preparation cartridge with thermal cycler and 1-color, 3-chamber RT-PCR. The system is designed such that the operator needs only to load the patient’s nasopharyngeal swab sample with lysis buffer into the cartridge, and then the entire sample preparation and molecular diagnosis can be automatically completed within 2.5 hours. The cartridge can precisely dispense aliquots for multi-chambered PCR detection. The performance of the all-in-one system is comparable to commercial real-time PCR instruments with manual RNA extraction and purification. In addition, the multi-chambered PCR capability and sensitivity of the all-in-one system for influenza diagnosis have been verified with clinical seasonal H1N1 influenza samples and control experiments. Lastly, in order to enhance the detection capability, a multiplexing PCR device has been developed for rapid filling/sealing of PCR mixture. The system allows for the detection of up to 100 targets in one run. The performance of the chip has been successfully tested in two processes using isothermal PCR.